DAMPAK PENGAWASAN DAN MOTIVASI TERHADAP DISIPLIN BELAJAR MAHASISWA - Katim, Katim (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this paper is to examine the effect of supervision and motivation on discipline. Survey methodology was used to obtain self-report data from a sample of 90 students in courses at a public university. Results revealed that supervision and motivation have a positive correlation with discipline. Indicates that the more effective supervision and motivation, the higher the student's discipline will be. Implications and suggestions are discussed in the paper. Keywords: supervision, motivation, discipline